Pengaruh Campuran Ekskreta Ayam Petelur dan Serasah Dedaunan pada Vermicomposting terhadap Nisbah C/N dan Penyusutan Vermicompost - Atika Amalia Dewi; Eulis Tanti Marlina; Yuli Astuti Hidayati (Unpad Press, 2022)
Management of layer excreta and leaf litter can be done by using the vermicomposting method that utilizes the activity of earthworms and microorganisms. The activity of earthworms and microorganisms will reduce the C/N ratio and shrinkage in vermicomposting. This study aimed to determine the effect of a mixture of layer excreta and leaf litter on vermicomposting to the C/N ratio and shrinkage in vermicompost. This study used an experimental method with a completely randomized design (CRD), with three C/N ratio treatments, namely T1 (25), T2 (30), and T3 (35) with six replications. Further analysis using Duncan's multiple distance test. The process begins with initial decomposition for 14 days, followed by vermicomposting for 14 days. The results showed that the C/N ratio during vermicomposting reached 17.84 – 33.23 with shrinkage ranging from 15.00% - 33.50%.